Equations of mechanics of growing viscoelastic solids - Nikabadze, Mikheil; Mardaleishvili, Nodar; Kikvidze, Omar (Bulletin of Akaki Tsereteli State University, 2024)
The article presents boundary value problems for growing viscoelastic solids. Determining equations for non-growing (basic) solids are written. Equilibrium equations for growing solids are written, and boundary conditions are stated at small deformations on the boundary of the dividing surface of the main and additional bodies.